Síntese e avaliação da atividade biológica de compostos de ouro(I) com ligantes ditiocarbamato - Thaiz Cristina Soares dos Santos (2024)
Cancer is the general term used to describe a group of more than 100 diseases, characterized by the uncontrolled growth of cells that tend to invade neighboring tissues and organs. Cancer is one of the most urgent challenges in global public health, being one of the leading causes of death and, consequently, a significant obstacle to increasing life expectancy, as it is one of the top causes of motality worldwide. However, the scientific community is constantly searching for new drugs with antitumor activity that demonstrate greater efficacy and high selectivity in treating various types of cancer. Gold(I)-based drugs have been extensively studied and tested in cancer chemotherapy since the discovery of the antitumor properties of auranofin in in vitro studies against various tumor cell lines. However, toxic side effects and intrinsic or acquired cellular resistance in some patients due to the administration of these gold compounds compromise their effectiveness and stimulate the search for analogs with a more favorable profile of effects. This work presents the synthesis and structural characterization of three novel gold(I) complexes with the general formula [Au(DTC)PPh3], where DTC are ligands derived from dithiocarbamate and PPh3 is triphenylphosphine, aiming to obtain potential antitumor agents. The characterizations were performed using elemental analysis, thermogravimetric analysis, infrared and UV-VIS absorption spectroscopy, 1H, 13C, and 31P NMR spectroscopy, mass spectrometry, and single-crystal X-ray diffraction. The interaction of the synthesized complexes with DNA and BSA (bovine serum albumin) was also evaluated through spectrophotometric and fluorimetric assays and agarose gel electrophoresis, with the results obtained showing some interaction of the compounds with these biological targets. The antiproliferative activity of the compounds was evaluated against breast cancer cell lines (MDA-MB-231 and 4T1) and a non tumorigenic breast cell line (MCF-10a), demonstrating the enhancement of cytotoxic action after complexation with gold. All three complexes exhibited promising activity, particularly the 4-Oxopiperidine-1 carbodithioate Gold(I) triphenylphosphine complex, which showed excellent activity against the 4T1 cell line with IC50 = 0.89 ± 0.01 µM, IS = 2.7. Therefore, the results presented provide significant contributions to the literature and may aid in the development of gold compounds as prototypes for metallodrugs.